1981
DOI: 10.3181/00379727-166-41066
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency and Elastin Metabolism in Avian Lung

Abstract: Copper deficiency in the chick causes anatomical changes in lung that are characterized by an apparent thinning of the air-blood capillary network of tertiary bronchi. Although the net content of the elastin in lung was not changed significantly by nutritional copper deficiency, it was possible to demonstrate an increase in the lysine content and a decrease in the desmosine content of lung elastin from copper-deficient chicks compared to that from controls. Further, the content of soluble elastin was also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Lysyl oxidase, a copper-dependent enzyme, plays a central role in the formation of secondary septa and thus lung maturation [14][15][16][17][18]. It can therefore be expected that a decrease in the copper content of the developing lung will result in a slower lung development or that copper supplementation may enhance lung maturation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lysyl oxidase, a copper-dependent enzyme, plays a central role in the formation of secondary septa and thus lung maturation [14][15][16][17][18]. It can therefore be expected that a decrease in the copper content of the developing lung will result in a slower lung development or that copper supplementation may enhance lung maturation.…”
Section: Discussionmentioning
confidence: 98%
“…Lysyl oxidase plays a key role in the cross-linking of elastin and the conversion of soluble elastin into insoluble elastin. Copper is an essential component of lysyl oxidase [14,15], and, thus, a deficiency of copper could then be expected to result in a metabolic defect, such as an increase in the soluble component of the protein and a decrease in the insoluble component [16]. Cross-linking of elastin may be crucial in further partitioning of the primitive alveolar sacs during alveolarization, and it has been shown that for some organs, particularly at specific periods of organogenesis (e.g., formation of the aorta or transition from a saccular to an alveolar lung), any impairment of the lysyl oxidase activity is critical [17,18].…”
mentioning
confidence: 99%
“…More information is needed to demonstrate that the proposed elastin types do not arise from genetic polymorphisms. With respect to lung, the observations to date (11,33,42) suggest that chick aorta and lung tropoelastin are nearly identical in size and have similar chemical properties and composition (Table 1). There also appear to be close similarities between sheep nuchal ligament and sheep lung elastin (15,41).…”
Section: Components Of Elastic Fiber: Isolation and Composition Of Elmentioning
confidence: 97%
“…First, it is clear from examination of composition data that 3 to 8% of the total prolyl residues in elastin are hydroxylated (5,33,56). However, unlike collagen the lysyl residues in elastin are not hydroxylated and the hydroxylation of proline does not Figure 2 are indicated.…”
Section: Post-translational Steps In Elastic Fiber Formationmentioning
confidence: 99%
See 1 more Smart Citation